Fostering a Sustainable Future in Somalia: Examining the Effects of Industrialization, Energy Consumption, and Urbanization on Environmental Sustainability - Abdi, Abdikafi Hassan; Hashi, Mohamed Ahmed (International Journal of Energy Economics and Policy, 2024)
While existing research has extensively explored the individual impacts of energy consumption, industrialization, and urbanization on environmental sustainability, there remains a notable gap in understanding the synergistic effects of these factors within the context of rapidly developing regions, such as Somalia. Therefore, this study explores the impacts of energy consumption, industrialization, and urbanization on environmental sustainability in Somalia from 1990 to 2020. The long-run linkage among the variables of the study was confirmed using the bounds-testing approach. The findings from the ARDL model indicate that economic growth, energy consumption, and trade openness significantly exacerbate environmental pollution in Somalia in the short- and long-run. Conversely, while industrialization and urbanization reduce environmental pollution both the short- and long-run, urbanization does not demonstrate a statistically significant impact. The long-run findings of the study were validated using the DOLS and FMOLS approaches. The Granger causality analysis reveals unidirectional causalities from environmental pollution to GDP per capita, industrialization, and trade openness, as well as from energy consumption to environmental degradation. However, no causal linkage is detected between urbanization and environmental pollution within Somalia. Based on the results of the study, we propose the promotion of renewable energy sources, green industrialization strategies, urban planning and sustainable development, and enhanced monitoring and regulation to effectively address environmental degradation.